Protective effect of sodium ascorbate on odontoblast-like cells MDPC-23 exposed to a bleaching agent - Lima, Adriano Fonseca de; Lessa, Fernanda Campos Rosetti; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP]; Marchi, Giselle Maria (My University, 2010)
To evaluate the cytotoxic effects of a bleaching agent composed of 0.01% carbamide peroxide (CP; 2.21μg/ml H2O2) on the MDPC-23 odontoblastic cell line, and to determine whether sodium ascorbate (SA) is capable of reducing, or even eliminating, the toxic effects caused by this bleaching agent. Methods: The cells were seeded in wells and incubated for 48 hours. CP and SA were dissolved in a culture medium (DMEM) in order to obtain experimental extracts. Six groups of cells (n=10) were treated as follows: G1: no treatment (control); G2: 0.25 mM SA/60 min; G3: 0.5 mM SA/60 min; G4: 0.25 mM SA+0.01% CP/60 min; G5: 0.5 mM SA+0.01% CP/60 min; and G6: 0.01% CP/60 min. The cell metabolism was evaluated by MTT assay, and the cell morphology was assessed by scanning electron microscopy. The data obtained were analyzed by 2-way ANOVA and post-hoc Tukey’s test (α=5%). Results: The percentages of cell metabolism were as follows: G1 (control)=100%; G2=110.06%, G3=108.57%, G4=90.35%, G5=97.63%, and G6=66.88%. Group 6 presented a statistically lower cell metabolism than did the other groups, and the cells that remained on the substrate exhibited changes in their morphology. SA decreased the cytotoxic effects caused by CP, demonstrating its protective effect against the toxic components of this dental product. Conclusions: It was concluded that CP gel has cytopathic effects on MDPC-23 odontoblastic cells, even at low concentrations such as 0.01%. SA at 0.25 mM, and that 0.5 mM is able to protect these cultured cells against the cytotoxic effects of CP.
Keywords: Bleaching agent; Carbamide peroxide; Odontoblasts; Sodium ascorbate; Cytotoxicity